Remediation of Oil Production by Matrix Acidizing Method on an Oil Well - Kasi, Njeudjang; Justine, Yandjimain; Madeleine, Nitcheu; Théophile, Ndougsa-Mbarga (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
The remediation oil production by matrix acidizing method on the well named "X" (for confidential reasons) is scrutinized in this paper. Initial production of 1150 bpd, production index of 2.8 STB/Psi/d and permeability of 150md, in 2018 two years down the lane this dropped to 450 bpd, production index 0.7 STB/Psi/d. The declined observed on the production index is trouble shouted and after elimination of (no completion damage/perforation damage), the skin is calculated by carrying out a well test (build-up test) whose extrapolation in excel over times gave us a skin of 40.The reservoir heterogeneity, containing >20% of feldspar, carbonates and paraffin’s guided thematrix acidizing design and treatment proposition to remedy this problem. A positive displacement pump (HT400), boosted by a centrifugal pump were used to pump the acid treatment through high pressure treating line downhole. Halliburton insite for stimulation the (IFS) software monitored treating pressure and surface flow rate, keeping injection rate below fracturing pressure. PipeSim software is used to run the nodal analysis before and after treatment this helped to forecast optimal production rates and pressure after treatments. Matrix acidizing method applied on the well X increased the production to 850 bpd with production index of 2 STD/psi/d, skin - 1.5. The economic benefit to the company stood at (profit oil 21,699,500 USD.) over a two years period of production. Meanwhile uncertainties in demand and supply of crude oil at the international market cause constant fluctuation in oil prices, this should be strongly considered upon execution of this project. Overall applications of this acidizing treatment can be carried out on reservoirs with similar mineralogy. HCl/HF blend dissolves sandstone, mud stone and calcite minerals thus reservoir porosity and permeability can be enhanced in regions extending several meters around the injection well.